Ethical Pluralism in Islamic Thought: Reassessing Classical Jurisprudential Diversity for Contemporary Multicultural Governance - Khusni Alhan; Roni Susanto; Robbin Dayyan Yahuda (Harmony Philosophy: International Journal of Islamic Religious Studies and Sharia, 2025)
This study explores the relevance of classical Islamic jurisprudential diversity, particularly through the concept of ikhtilāf (juristic disagreement), in contributing to contemporary governance models in multicultural societies. The historical flexibility within Islamic legal thought has provided a robust foundation for ethical pluralism, which can support inclusive governance by recognizing and respecting diverse legal, cultural, and religious traditions. The concept of ikhtilāf encourages a pluralistic approach to law, allowing multiple interpretations of Islamic law to coexist, which is particularly beneficial in multicultural contexts where legal pluralism is often necessary. The study also highlights the challenges of integrating rigid interpretations of Islamic law with the dynamic needs of modern societies, particularly in areas such as human rights and gender equality. By examining real world case studies from Muslim majority and Muslim minority contexts, such as Malaysia and the UK, the study underscores the importance of adapting Islamic jurisprudence to contemporary governance while ensuring social cohesion and justice for all communities. The research further emphasizes the need for legal reforms that integrate the principles of ikhtilāf into both Muslim majority and multicultural societies, providing a more inclusive and just framework for governance. Finally, the study suggests that future research should focus on expanding the integration of ethical pluralism into contemporary political systems, considering both Islamic and secular legal frameworks for a cohesive governance model.